Efficacy of combined phenotypic methods for methicillin-resistant Staphylococcus aureus detection and antibiotic susceptibility - Shah, Aliya; Peerzada, Bushra; Singh, Varsha A.; Garg, Ritu; Zaman, Muzzafar; Shah, Akif Mutahar (International Journal of Research in Medical Sciences, 2022)
Background: The main aim of our study is to demonstrate comparative evaluation of oxacillin disc diffusion (ODD), oxacillin screen agar (OSA), CHROM agar (CA) with cefoxitin disc diffusion (CDD) method for the detection of methicillin-resistant Staphylococcus aureus obtained from various clinical samples. Methods: This prospective study was conducted to detect Methicillin resistance among staphylococcus aureus by four phenotypic methods isolated from various clinical samples received in the Department of microbiology MMIMSR, Mullana. Results: The data was statistically analyzed, compiled in form of tables, graphs, percentage and test of significance will also be done wherever necessary (using Microsoft Excel, 2008 version) CDD+ODD+OSA+CA proved to be 100% followed by ODD+OSA+CA and CDD+OSA+CA 82.07% and CDD+ODD+OSA 80.1%. Conclusions: Combined phenotypic methods are better in evaluating and studying MRSA infections in hospitals as compared to tests done in isolation for proper diagnosis and timely treatment of infections.